Immigration in American Economic History - Abramitzky, Ran; Boustan, Leah (Journal of Economic Literature, 2017)
The United States has long been perceived as a land of opportunity for immigrants. Yet, both in the past and today, US natives have expressed concern that immigrants fail to integrate into US society and lower wages for existing workers. This paper reviews the literatures on historical and contemporary migrant flows, yielding new insights on migrant selection, assimilation of immigrants into US economy and society, and the effect of immigration on the labor market.